Study of the Impact of Aerobic Digestion on the Waste Sludge Dewaterability of SBR System of Yazd Wastewater Treatment Plant - Masoud Taheriyoun; Behzad Aghababaei; Sajad Mohammadi; Vahid Ghelman; Akbar Salehi Vaziri (علوم و مهندسی آب و فاضلاب, 2022)
Sludge treatment and disposal processes in wastewater treatment plants account for a significant portion of the total treatment costs. One of the most expensive parts of sludge treatment is chemical conditioning. Study of the effect of process chain on the conditioning and dewaterability can effectively optimize and reduce operating costs and increase the quality of effluent sludge. This paper investigates the impact of aerobic digestion of waste sludge in Yazd wastewater treatment plant by SBR method on its dewaterability. For this purpose, the waste sludge sample of the plant was aerated in the laboratory at different residence times from 1.5 to 7 days. Then the dewaterability of the sludge was measured by two methods of Specific Resistance to Filtration (SRF) and Tests of Time of Filtration (TTF) in two cases with and without chemical conditioning with cationic polyacrylamide. The results showed that sludge aeration for up to 3 days without conditioning led to the best sludge dewaterability. The best results were obtained at 1.5 days aeration for the conditioning mode with polymer, which improved the dewaterability up to 4.5 times in the optimum polymer dosage. In this case, the polymer dosage decreased by 30% compared to the non-aerated conditioned sludge. It indicates the effect of digestion retention time on dewaterability. At the beginning of the process, the decomposition of cellular material improves the release of water from solid particles. Still, its continuation reduces the dewatering capability due to reduced particle size and conversion to colloidal materials.